Establishment and characterization of the immortalized porcine lung-derived mononuclear phagocyte cell line - Takenouchi, Takato; Masujin, Kentaro; Suzuki, Shunichi; Haraguchi, Seiki; Hiramatsu, Kanae; Kokuho, Takehiro; Uenishi, Hirohide (Frontiers in Veterinary Science, 2022)
Mononuclear phagocytes (MNP), including monocytes, dendritic cells (DC), and macrophages, play critical roles in innate immunity. MNP are abundant in the lungs and contribute to host defense against airborne agents and pulmonary immune homeostasis. In this study, we isolated porcine lung-derived MNP (PLuM) from primary cultures of parenchymal lung cells and then immortalized them by transferring the SV40 large T antigen gene and porcine telomerase reverse transcriptase gene using lentiviral vectors. The established cell line, immortalized PLuM (IPLuM), expressed DC/macrophage markers; i.e., CD163, CD172a, and major histocompatibility complex class II, whereas they did not express a porcine monocyte-specific marker, CD52. The expression patterns of these cell surface markers indicate that IPLuM originate from the DC/macrophage lineage rather than the monocyte lineage. The bacterial cell wall components muramyl dipeptide and lipopolysaccharide induced the production of the interleukin-1 family of pro-inflammatory cytokines in IPLuM. Phagocytotic activity was also detected by time-lapse fluorescence imaging of live cells when IPLuM were cultured in the presence of pHrodo dye-conjugated E. coli BioParticles. It is worth noting that IPLuM are susceptible to African swine fever virus infection and support the virus' efficient replication in vitro. Taken together, the IPLuM cell line may be a useful model for investigating host-agent interactions in the respiratory microenvironments of the porcine lung.